PSI-B-42 Late-Breaking: Effect of Nellore cattle supplementation during the growing phase on pasture with urea (high or low) and with or without tannin extracts on the performance, ruminal fermentation and blood parameters. (5th December 2019) - Cidrini, Iorrano A; Prados, Laura; Foresto, Willian; Mariano, Eduarda; Souza, William; Siqueira, Gustavo R; Resende, Flavio D
Abstract: The objective of this experiment was to evaluate the effect of cattle supplementation (3g/kg BW) with urea (U) and tannin extracts (TE; SilvaFeed Bypro®️) during the dry season on performance, ruminal fermentation and blood parameters. Trial 1-Sixty-four Nellore (294 ± 15.2 kg BW) were used to determine the effect of supplementation during the growing phase (137d) on performance. The animals were blocked by BW to one of four treatments: 1) 30g urea/kg DM supplement (LU); 2) 30g urea/kg DM supplement + 7g TE/kg DM supplement (LU+TE); 3) 50g urea/kg DM supplement (HU); 4) 50g urea/kg DM supplement + 7g TE/kg DM supplement (HU+TE). Trial 2- Eight ruminally cannulated Nellore fed with trial 1 diet (4 x 4 Latin square) was used to evaluate DM intake and digestibility, ruminal pH, VFA, ruminal ammonia, serum glucose and urea at different times after feeding. The data were analyzed by ANOVA using PROC MIXED, SAS 9.4. There was no interaction (P > 0.10) between U and TE, the treatments did not affect (P > 0.10) ADG, intake or digestibility, VFA total, serum glucose and urea (Table1). However, animals fed TE showed butyrate (Figure 1) tended to higher on time 12-18h (Time × TE; P = 0.06), while the acetate: propionate ratio tended (Time × TE; P = 0.08) to decrease. The isovalerate tended to be higher on time 6h in animals fed HU+TE while LU+TE tended to be higher on time 12-18h. The ruminal pH of the animals fed with LU tended to be lower on time 6h compared to HU, while ruminal ammonia was higher (P < 0.01) to animals fed HU on time 6h compared to LU. Overall, TE and U did not influence the performance of Nellore and the inclusion of TE tended to improve the efficiency in ruminal fermentation.